2019
DOI: 10.1186/s12986-019-0356-5
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein ameliorates palmitic acid-induced lipotoxicity and oxidative dysfunction in H9c2 cardiomyoblast cells via ROS suppression

Abstract: Background High levels circulating saturated fatty acids are associated with diabetes, obesity and hyperlipidemia. In heart, the accumulation of saturated fatty acids has been determined to play a role in the development of heart failure and diabetic cardiomyopathy. High-density lipoprotein (HDL) has been reported to possess key atheroprotective biological properties, including cellular cholesterol efflux capacity, anti-oxidative and anti-inflammatory activities. However, the underlying mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 61 publications
3
70
0
Order By: Relevance
“…Additionally, LXR is known to elevate cholesterol levels in peripheral cells, the liver, and the intestine, which results in an overall net increase in cholesterol mobilization and catabolism, thus making LXR a pharmaceutical target for therapeutic intervention for the treatment of hypercholesterolemia and atherosclerosis. Indeed, several research groups identified agents that can reduce atherosclerosis without activating SREBP-1c or increasing hepatic lipogenesis, such as taurine, taurine, ethyl 2,4,6-trihydroxybenzoate, WAY-252623, and N,N-dimethyl-3β-hydroxy-cholenamide [32,35,36]. Indeed, sesamin enhances cholesterol efflux from RAW264.7 macrophages as reported by Liu et al [37].…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 88%
“…Additionally, LXR is known to elevate cholesterol levels in peripheral cells, the liver, and the intestine, which results in an overall net increase in cholesterol mobilization and catabolism, thus making LXR a pharmaceutical target for therapeutic intervention for the treatment of hypercholesterolemia and atherosclerosis. Indeed, several research groups identified agents that can reduce atherosclerosis without activating SREBP-1c or increasing hepatic lipogenesis, such as taurine, taurine, ethyl 2,4,6-trihydroxybenzoate, WAY-252623, and N,N-dimethyl-3β-hydroxy-cholenamide [32,35,36]. Indeed, sesamin enhances cholesterol efflux from RAW264.7 macrophages as reported by Liu et al [37].…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 88%
“…Our previous results show that food ingredients and phytochemicals exhibit various diverse biological activities [37][38][39][40][41]. Particularly various phytoextracts and their active principles have shown to provide effective cardioprotection against various challenges [42][43][44][45][46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…After blocking the blots with 4% of bovine serum albumin, they were treated with primary antibody (1:2000) then secondary antibody (1:2000). Enhanced chemiluminescent imaging of the blots was visualized by the UVP Biospectrum system (UVP, Upland, CA, USA) 16‐18 …”
Section: Methodsmentioning
confidence: 99%